IMPLEMENTASI BUDAYA LITERASI TERHADAP PENINGKATAN HASIL BELAJAR BIOLOGI SISWA KELAS X SMA NEGERI 4 JAYAPURA - Joko Waluyo; TIURLINA SIREGAR (Jurnal Ilmu Pendidikan Indonesia, 2018)
The purpose of the study was to determine the implementation of literacy culture to increase learning outcomes in the material of the scope of biology of class X SMA Negeri 4Jayapura.The method in this study is furpossive sampling method and data collection techniques that will be used in the form of a questionnaire (questionnaire), namely data collection techniques carried out by giving a set of questions or written statements to respondents.The results of this study are partially literacy culture does not have a significant effect on learning outcomes of the material scope of biology because based on the results of simple regression test obtained t count <t table (0.075 <1.960) or significant t> 5% (0.940> 0.05) with regression equation Y = 72,958 + 0.007 X3 with a contribution or relative contribution of 0.00%. There is an increase in the learning outcomes of the biological scope of class X students of SMA Negeri 4Jayapura, where the average n-Gain test is obtained at 0.52 in the medium category.  Keywords: Implementation, Culture, Literacy, Biology.